Prevalence of low birth weight and its associated factors: Hospital based cross sectional study in Nepal - Pratibha Thapa; Amod Poudyal; Rajan Poudel; Dipak Prasad Upadhyaya; Ashish Timalsina; Rama Bhandari; Jijeebisha Baral; Rabindra Bhandari; Prakash Chandra Joshi; Pratiksha Thapa; Nabin Adhikari (Public Library of Science (PLoS), 2022)
Low birth weight is still an important public health problem worldwide. It is a major contributor to neonatal death in developing countries, including Nepal. The government of Nepal has developed and implemented different programs to improve maternal and neonatal health, including baby's birth weight. However, low birth weight is a major maternal and child health challenge. Maternal factors determining the birth weight of neonates have been poorly assessed in previous studies in Nepal. Thus, this study aims to assess the prevalence and risk factors associated with low birth weight in Nepal. An institution-based descriptive cross-sectional study was carried out in Paropakar Maternity Hospital and Tribhuvan University Teaching Hospital of Kathmandu district among 308 postnatal mothers. The data was collected through the face-to-face interview technique. The data was entered in EpiData 3.1 and exported to Statistical Package and Service Solutions version 21 for analysis. Multivariate logistic regression was used to obtain an adjusted odds ratio, while p-value < 0.05 with 95% Confidence Interval (CI) was considered significant. The findings showed that 15.3% of the children had low birth weight. The mean and standard deviation of childbirth weight was 2.96±0.59 kg. Mothers belonged to Dalit ethnic (AOR = 2.9, 95% CI = 1.2-7.1), Antenatal Care visited three or fewer (AOR = 2.6, 95%CI = 1.0-6.6) and did not comply with Iron and Folic Acid supplementation (AOR = 2.1, 95% CI = 1.0-4.4) were significantly associated with low birth weight. Nearly one in every six children had low birth weight. Maternal health services such as antenatal care and compliance with a recommended dose of maternal micronutrients significantly impact on birth weight. Maternal and neonatal health programs should consider these factors to reduce adverse birth outcomes in Nepal.